디자인 액티비즘 교육 모델 설계 연구 - 캡스톤디자인 교과의 ‘DA+R DA+B 프로젝트’를 중심으로 - 한희석(Hee Seok Han); 박상희(Sang Hee Park) (예술· 디자인학연구, 2024)
사회 수요와 산업구조 및 기술의 변화에 따라 본질적인 사고와 고안을 기반으로 다양한 문제를 발굴하고 해결하기 위한 솔루션을 제시하는 캡스콘 디자인의 중요성이 대두되어 왔다. 본 연구의 교육 모델은 디자이너가 주체적으로 현 상태의 문제를 발견하고 해결하는 과정을 하나의 실천적 방법론이자 사회적 활동으로 도출하고 수행하기 위함에 목적이 있다. 본 연구는 2021년부터 진행되어 왔던 교과목을 바탕으로 디자인 액티비즘의 개념과 유형을 접목하여 개발된 독자적인 교육 모델 다답(DA+R DA+B) 프로젝트의 설계와 지도 방법론을 다룬다. 이를 위하여 디자인학과의 캡스톤디자인 과정에 PBL 모델의 설계를 정교화하고 이를 바탕으로 사회와 환경, 경제 등 SDGs 관점의 변화로 유도하고 개선하고자 하는 디자인의 본질적 행위의 디자인 액티비즘 교육 모델 기반의 새로운 프로젝트로 재정의하고 설계하였다. 더불어 본 모델의 목표 달성에 필요한 요소, 환경, 운영을 위한 지침 등에 대한 학습자 설문으로 프로젝트의 전 과정에서의 검증 및 분석을 실행하였다. 본 연구는 디자인 액티비즘 교육 모델을 통해 사회의 변화 및 수요에 대응할 수 있는 창의적 문제해결 기반의 디자인 교육 방법론을 제시하고자 한다. In the field of design, in response to changes in social demand, industrial structure, and technology, the importance of Capscon design is increasing to present solutions to discover and solve various problems based on essential thinking and design rather than just visual or formative expressions of the past. has come to the fore. This study elaborated the design of the PBL model in the capstone design course of the Department of Design and redefined it as a new project based on the design activism education model of the essential behavior of design to induce and improve changes in the perspective of SDGs such as society, environment, and economy. and designed it. The purpose of this educational model is to derive and perform the process of designers independently discovering and solving current problems as a practical methodology and social activity. This study deals with the design and guidance methodology of the DA+R DA+B project, an independent educational model developed by combining the concepts and types of design activism based on the Capstone Design subject of the Department of Design, which has been in progress since 2021. In addition, through a survey on the elements necessary to achieve the goals of this educational model, the learning environment, and practical guidelines, we conducted verification and analysis of how learners carry out projects and produce results over the course. Through this model, we aim to present design education and research methodology based on creative problem solving that can respond to social changes and demands. KCI Citation Count: 0